2019
DOI: 10.3389/fimmu.2019.02010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control of Innate Lymphoid Cell Migration

Abstract: Innate lymphoid cells (ILCs) are specialized immune cells that rapidly respond to environmental challenges, such as infection and tissue damage. ILCs play an important role in organ homeostasis, tissue repair, and host defense in the mucosal tissues intestine and lung. ILCs are sentinels of healthy tissue function, yet it is poorly understood how ILCs are recruited, strategically positioned, and maintained within tissues. Accordingly, ILC migration is an area that has recently come into focus and it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 143 publications
(249 reference statements)
0
52
0
Order By: Relevance
“…The approximate concentration of metabolites reflecting the physiologic state is difficult to determine. The concentration of metabolites varies according to the microenvironment (43), and there is usually a great difference between intracellular and extracellular levels. Taurine is found in low levels in plasma and extracellular fluids (range 10-100 μM), but exhibits high intracellular concentrations, reaching up to 50 mM (44).…”
Section: Discussionmentioning
confidence: 99%
“…The approximate concentration of metabolites reflecting the physiologic state is difficult to determine. The concentration of metabolites varies according to the microenvironment (43), and there is usually a great difference between intracellular and extracellular levels. Taurine is found in low levels in plasma and extracellular fluids (range 10-100 μM), but exhibits high intracellular concentrations, reaching up to 50 mM (44).…”
Section: Discussionmentioning
confidence: 99%
“…ILC3s are heterogeneous but consistently require transcription factor RORγt for their development and function. LTis are related to ILC3s with distinct functions in the secondary lymphoid organ formation during both embryonic and adult stages of development (8,11,20). In general, these cells found in adult mice are termed LTilike cells, which have a similar phenotype to LTis (21).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the functional association with ILC3s, LTis are considered a separate ILC lineage. Fetal liver-derived LTiPs express α4β7 integrin and C-C Motif Chemokine Receptor 6 (CCR6), whereas adult LTis derived from bone marrow precursors display upregulated RORγt in a Notch-dependent manner (9,20). Adult mice also have T-bet-expressing CCR6 − NKp46 + ILC3s derived from CCR6 − NKp46 − ILC3s (23) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…GPR183 played vital role in cell communication, migration and development of lymphocytes [16,17]. Recently, some studies have found GPR183 mediated intestinal immunity and in ammation by inducing migration and development of Group 3 innate lymphoid cells(ILC3s) [18][19][20]. Though GPR183 has intimate connection to body immunity, its role in tumor immunity remains mysterious.…”
Section: Introductionmentioning
confidence: 99%